Analysis of Distribution Patterns and Diversity of Dragonflies (Odonata) in Kerandangan Nature Tourism Park - Khusnul Fajriansyah; I Putu Artayasa; Gde Cahyadi Wirajagad; Mohammad Liwa Ilhamdi (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Dragonflies (Odonata) are bioindicators of environmental quality that are sensitive to changes in habitat conditions. This research aimed to analyze the dragonfly species found in the Kerandangan Nature Tourism Park, analyze their distribution patterns, and determine their diversity level. The research was conducted in three observation blocks, namely utilization, rehabilitation, and protection blocks. Sampling in this study was conducted using the line transect method with direct field observation. Distribution patterns were analyzed using the dispersion index, while diversity was measured using the Shannon–Wiener index (H’). The results showed that 18 dragonfly species belonging to 8 families were identified. The distribution patterns of dragonflies, both overall and within each block, tended to be clumped. The dragonfly diversity index (H’) in the Kerandangan Nature Tourism Park was 2.12, indicating that the ecosystem is relatively stable. In addition, damselflies (Zygoptera) were only found in the utilization block, which has water sources, and were absent in the rehabilitation and protection blocks. This finding suggests that abiotic and biotic environmental factors influence the presence and distribution of dragonflies in the study area. This research is expected to contribute scientific information to support enviromental management and conservation efforts in the Kerandangan Nature Tourism Park.